Test of ball speed in table tennis based on monocular camera - Zhang, H.; Kong, L.-H.; Guan, Y.-P.; Hu, J.-J. (Proceedings of the 10th International Symposium on Computer Science in Sports (ISCSS), 2016)
This paper has designed and developed a platform for testing table tennis ball speed, which are used in the tests of 5 top Chinese female table tennis players in three of their practices. The results show that the ball speeds of LI and DING are faster than those of LIU, ZHU and CHEN. LI`s ball speed over the net is the fastest in all exercises, especially in forehand loop-drive against backspin and forehand moving loop-drive. DING`s ball speed over the net is the second-fastest in different practices (except for forehand loop-drive in the Two to One practice). LIU, ZHU and CHEN`s ball speeds are slower, among which, the relatively slower ball speeds over the net were LIU`s backhand loop-drive in the Two to One practice, ZHU`s forehand loop-drive in the Two to One exercise and in the forehand loop-drive against backspin, and CHEN`s forehand moving loop-drive.